THERAPEUTIC DOSAGE RANGES AND CHRONIC ADVERSE EFFECTS OF TACROLIMUS IN THAI KIDNEY TRANSPLANT PATIENTS - BOONSOM, SUTHIDA; VANNAPRASAHT, SUDA; PREECHAGOON, YUPAPORN (International Journal of Applied Pharmaceutics, 2021)
Objective: This study proposed to study the therapeutic dosage ranges and to determine the prevalence of and the risk factors for the adverse effects of Thai tacrolimus-based therapy kidney transplant patients. Methods: The fifty-nine kidney transplant patients who had kidney transplantation between January 2016 and May 2018 and were non-diabetic, non-hypertension, and normal kidney parameters before kidney transplantation were enrolled and followed up for 6 months. Data on graft rejection episodes and three significant adverse effects of tacrolimus, nephrotoxicity, hypertension (HTN), and post-transplant diabetes mellitus (PTDM) at each time point were recorded and analyzed. Results: The range and mean (±standard deviation) of tacrolimus troughs level for the 204 points were 3.9–10.2 ng/ml and 6.4±1.8 ng/ml, respectively. About 73% of patients had HTN, 61% were on antihypertensive drugs, and 32% had PTDM. Seven patients (12%) proved to have allograft rejection by kidney biopsy. Only four patients did not have any three adverse effects. Similarly, laboratory parameters (SCr, BUN, and blood pressure) were identical during each period. All patients received prednisolone and mycophenolate mofetil as part of the comedication immunosuppressive regimen. Conclusion: There was no significant difference between tacrolimus chronic adverse effects and therapeutic tacrolimus trough concentrations in Thai kidney transplant patients. Further investigations concerning pharmacokinetics and pharmacodynamics will be needed to improve the efficacy and safety of tacrolimus.